Solid-pseudopapillary tumour of the pancreas: A report of a rare case - Arora A; Mahale A; Paudel K (Wolters Kluwer Medknow Publications, 2008)
The solid pseudopapillary tumour (SPT) of the pancreas is an uncommon cystic pancreatic neoplasm mostly seen in young females. We present a large SPT in a 16-year-old female who presented with acute onset upper- and mid-quadrant abdominal pain associated with nausea and vomiting for 4 days. The lesion was demonstrated by abdominal ultrasound and by computed tomography, which was successfully removed surgically.